Sustainable AGP alternatives: a systems approach to non-antibiotic growth regulators standardization, synergistic formulation and environmental safety - Abbas, Manzar; Abbas, Ghulam; Fatima,; Hashmi, Abdullah Hassan; Jaffery, Seemab; Li, Yunxia; Zhao, Gaoping; Xihe, Li (Frontiers in Veterinary Science, 2026)
Growing consumer preference for livestock products labeled “Raised without Antibiotics” (RWA) or “No Antibiotics Ever” (NAE), escalating crisis of antimicrobial resistance due to long use of antibiotic growth promoters (AGPs) along with stringent regulatory restrictions, has intensified the demand for sustainable alternatives. This review summarizes recent advances in non-antibiotic strategies to enhance livestock production while aligning with global regulatory bans on in-feed antibiotics. We first delineate the multifunctional mechanisms of AGPs, primarily through gut microbiota modulation and immunomodulation, to establish a benchmark for alternative efficacy. The core analysis critically evaluates leading antibiotic substitutes, including probiotics, prebiotics, synbiotics, organic acids, dietary enzymes, and phytogenic food additives (PFAs). Among all, PFAs rich in terpenoids and phenolics for their antimicrobial, antioxidant, and gut health promoting properties along with cost-efficiency, scalability, and one health implications are preferred alternative to antibiotics. Further, we underscore emerging technologies such as antimicrobial peptides (AMPs), hyper-immune egg yolk antibodies (IgY), bacteriophages, genomic medicines, and clays and trace minerals, highlighting commercially approved examples like bacteriophage to control Salmonella. Despite demonstrated success in improving feed efficiency, growth performance, and overall animal health, challenges regarding consistency, bioavailability, and regulatory approval persist. The conclusive evidence positions a strategic combination of these natural and advanced alternatives, particularly optimized PFA formulations, as a viable and sustainable pathway to achieving antibiotic-free animal husbandry, thereby mitigating AMR risks and ensuring future food security.